Comparison of clinical and biochemical profile of obese and nonobese children - C. Patil, Lingaraja Gowda; S, Srinivas (International Journal of Contemporary Pediatrics, 2018)
Background: We compared clinical and biochemical parameters of obese children aged 6 to 18 years with normal controls visiting to outpatient department in a tertiary care hospital. It was a prospective case control study. Methods: Obese children with Body Mass Index > 2 standard deviation according to WHO chart were included. Endocrinological and syndromic obese children were excluded. We described risk factors for obesity and compared clinical and biochemical parameters between cases and controls. Student’s t test, Chi-square test and ANOVA (analysis of variance) were used for statistical analysis. Results: We noted higher prevalence of intake of junk food and sedentary lifestyle in obese group. Anthropometric parameters including BMI, skin fold thickness and abdominal circumference were higher in obese children compared to control group. Both systolic and diastolic blood pressures were high in obese children compared to control group. We observed higher prevalence of insulin resistance and dyslipidaemia among obese children. Conclusions: This study reemphasises that junk foods and sedentary lifestyle are important risk factors for obesity. Always screen for glucose intolerance, hypertension, insulin resistance and dyslipidaemia in obese children.